Primary renal malignant epithelioid angiomyolipoma with distant metastasis: a case report and literature review - Zhang, Jun; Wang, Wen-Juan; Chen, Li-Hong; Wang, Ning; Wang, Ming-Wen; Liu, Hao; Pang, Li-Juan; Jiang, Han-Guo; Qi, Yan (Frontiers in Oncology, 2023)
Epithelioid angiomyolipoma (EAML) is a rare type of mesenchymal angiomyolipoma with potential malignancy in the kidney that can cause lymph node metastases, local recurrence, and distant metastases. Herein, we describe a case of EAML in the right kidney of a 51-year-old man who was admitted to the hospital with a right abdominal mass. Computed tomography revealed a heterogeneously enhanced mass with blurred margins, which was considered malignant tumor. The radical nephrectomy was then performed. Two years later, the patient developed liver metastases from EAML and was administered sintilimab combined with bevacizumab.The patient survived after six months of follow-up. Histologically, the tumors showed clear boundaries and no obvious capsules. The tumor tissue mainly consisted of epithelioid tumor cells, thick-walled blood vessels, and a small amount of adipose tissue. Tumor cells with lipid vacuoles and acinar areas were large, round or polygonal, eosinophilic, or transparent in the cytoplasm. The enlarged and hyperchromatic nuclei were accompanied by distinct nucleoli and pathological mitosis. These histopathological findings resembled those of renal cell carcinoma, and immunohistochemical analysis was performed. The tumor cells were diffusely positive for HMB45, Melan-A, CK20, Vimentin antibodies, and TFE3, suggesting that the tumor originated from perivascular epithelioid cells, excluding renal cell carcinoma. The Ki-67 index was 10%. These histopathological features were observed in liver mass puncture tissues. We also summarized 46 cases of EAML with distant metastasis and explored the clinicopathological features of EAML to improve the treatment of the disease. EAML is often ignored in the clinical setting, leading to metastasis and recurrence. Therefore, EAMLs require long-term follow-up, and timely detection of recurrent disease can improve prognosis.